Arthroscopic Latarjet: 2 or 4 Cortical Buttons for Coracoid Fixation? A Case-Control Comparative Study. Issue 2 (February 2022) - Barret, Hugo; Chelli, Mikael; Van Der Meijden, Olivier; Langlais, Tristan; Boileau, Pascal
Background: While 2 screws are traditionally used for coracoid bone block fixation, no gold standard technique has yet been established when using cortical buttons. Purpose: To compare anatomic and clinical outcomes of the arthroscopic Latarjet procedure using either 2 or 4 buttons for coracoid bone block fixation. Study Design: Cohort study; Level of evidence, 3. Methods: A total of 23 patients with 4-button fixation (group 4B) were matched for age at surgery, sex, and follow-up to 46 patients who had 2-button fixation (group 2B). All patients underwent guided arthroscopic Latarjet (using coracoid and glenoid guides), and a tensioning device was used to rigidify the suture button construct and get intraoperative bone block compression. The primary outcome was assessment of bone block positioning and healing using computed tomography scans performed at 2 weeks and at least 6 months after surgery. The mean ± standard deviation follow-up was 49 ± 7 months (range, 24-64 months). Results: The bone block healing rate was similar in both groups: 91% in group 4B versus 95.5% in group 2B. The transferred coracoid was flush to the glenoid surface in 21 patients (91%) in group 4B and 44 patients (96%) in group 2B ( P = .6); it was under the equator in 22 patients (96%) in group 4B and 44 patients (96%) in group 2B ( P ≥ .99). There was no secondary bone block displacement; the rate of bone block resorption was similar between the groups: 28% in group 4B and 23% in group 2B ( P = .71). Patient-reported outcomes, return to sports, and satisfaction were also similar between the groups. The operating time was significantly longer in group 4B (95 vs 75 minutes; P = .009). Conclusion: A 4-button fixation technique did not demonstrate any anatomic or clinical advantages when compared with a 2-button fixation technique, while making the procedure more complex and lengthening the operating time by 20 minutes. A 2-button fixation is simple, safe, and sufficient to solidly fix the transferred coracoid bone block. The use of drill guides allows accurate graft placement, while the use of a tensioning device to rigidify the suture button construct provides high rates of bone block healing with both techniques (>90%).